A large patient study confirming that facioscapulohumeral muscular dystrophy (FSHD) disease expression is almost exclusively associated with an FSHD locus located on a 4qA-defined 4qter subtelomere. Issue 3 (20th September 2006) - Thomas, N S T; Wiseman, K; Spurlock, G; MacDonald, M; Üstek, D; Upadhyaya, M
Abstract : Facioscapulohumeral muscular dystrophy (FSHD), an autosomal dominant disorder, represents the third most common human muscular dystrophy. The FSHD disease locus, at chromosome 4q35, is associated with large contractions of the polymorphic repeat sequence array D4Z4 . In addition to FSHD disease association with large D4Z4 deletions, a biased interaction with a specific 4qter subtelomeric sequence has been described in patients. Two distinct 4qter subtelomeres, defined as types 4qA and 4qB, have been identified and shown to be equally prevalent in the Caucasian population. In almost all 4q35-linked patients with FSHD, however, disease expression only occurs when large D4Z4 deletions are located on 4qA-defined 4qter subtelomeres. Conversely, large D4Z4 repeat contractions situated on 4qB-defined subtelomeres either are not disease-causing or exhibit a greatly reduced disease penetrance. This study was initiated to confirm this direct FSHD disease association data by measuring the frequency of type 4qA-defined and 4qB-defined subtelomeric sequences in a large cohort of 164 unrelated patients with FSHD from Turkey and the UK, all known to have large D4Z4 deletions. An almost complete association was found between large D4Z4 repeat array deletions located on 4qA-defined 4qter subtelomeres and disease expression in our large FSHD patient cohort. The observed failure of probes 4qA and 4qB to hybridise to two patient-derived DNA samples confirms the presence of an additional rare type of 4qter subtelomeric sequence in humans.